Analisis Waste Pada Produksi Sari Kedelai Di UMKM XYZ Menggunakan Pendekatan Value Stream Mapping dan 5 Why Analysis - Nando, Fiky Two; Mayangsari, Adhindha Putri; Nursyabani, Inayah Aulia; Nurul, Sazhana; Ratih, Dwi; Ivan, Michael (Indonesian Journal of Engineering and Technological Innovation, 2025)
Production process efficiency is a crucial factor for micro, small, and medium enterprises (MSMEs) in enhancing competitiveness within the food industry sector. However, many MSMEs still face obstacles such as non-value-added activities (waste), including waiting time and inefficient material handling. This research aims to analyze and improve the production process of soybean juice at SME XYZ using the Value Stream Mapping (VSM) and 5 Whys methods. The VSM method is used to map the value stream in the production process in order to identify value-added activities, non-value-added activities, and necessary non-value-added activities. Meanwhile, the 5 Whys method is used to find the root causes of waste occurring on the production floor. The analysis results show that the main waste occurs in waste transportation and waste motion due to inefficient production layout and the absence of standard operating procedures. After improvements were made using the U-shaped layout design, there was a decrease in Non-Value Added activity time from 4,468 seconds to 2,270 seconds, and a decrease in lead time from 10,848 seconds to 8,650 seconds. Thus, the application of the VSM and 5 Whys methods proved effective in improving process flow efficiency and reducing waste in the production of soybean milk at UMKM XYZ.